Optimalisasi Produk Berbahan Dasar Pepaya Di Desa Karang Sari Dusun IV B Kecamatan Jati Agung Lampung Selatan - Yulianty; Emantis Rosa; Sri Wahyuningsih; Achmad Arifiyanto (CV. Multi Kreasi Media, 2023)
Papaya is one of the most widely cultivated plants in Indonesia. People generally use all parts of papaya in their daily lives, but not optimally yet, mainly only used as food and less varied While other parts such as fruit skin, seeds, and stems generally be thrown away as garbage. The skin and leaves could be used as liquid organic fertilizer and bio fungicide. Therefore, it is necessary to make an effort to optimize products from papaya plants in the community of Karang Sari Village IVB. This Community Service was carried out with the aim of knowing the utilization and increasing knowledge and practice of papaya plants. The results of the service obtained were the average pre-test score of 49.47 and the average post-test score of 95.79. There was an increase in points of 46.32. Further expectations in this service that the people in Karang Sari Village IV B can utilize papaya plants more varied and diverse.